Proses Manufaktur Pada Mesin Primer dan Sekunder PT XYZ Menggunakan Metode Linear Programming - Yurnalisdel Yurnalisdel (CV. Publikasi Indonesia, 2022)
The purpose of this study was to determine the manufacturing process on PT XYZ's primary and secondary machines using the Linear Programming method. This causes that in each period, the company experiences excess and decrease in production so that the company's profit is not optimal and results in large holding costs. This situation occurs because the company has been implementing production planning based on core. The method used as a solution is Linear Programming. The research method used is qualitative and descriptive methods and data collection techniques for library studies through various literature such as journals, books, magazines, articles obtained through Google Scholar with the keywords used namely manufacturing keywords, primary and secondary machines, and linear programming methods. so as to obtain accurate and in-depth data regarding the manufacturing process with the linear programming method. The results showed that the manufacturing process on PT XYZ's primary and secondary machines using the linear programming method could be more efficient in the use of existing resources and the policies implemented. So that feelings related to product combinations and changes related to profit per product with the loss of resources.